Periodic subwavelength ripples on a Si surface induced by a single temporally shaped femtosecond laser pulse: enhanced periodic energy deposition and reduced residual thermal effect. (9th July 2021) - Zhang, Yuchan; Cheng, Ke; Cao, Kaiqiang; Jiang, Qilin; Chen, Tianqi; Zhang, Shian; Feng, Donghai; Sun, Zhenrong; Jia, Tianqing
Abstract: In the fabrication of regular, uniform periodic ripples produced by femtosecond laser pulses, enhancing the periodic energy deposition and reducing the residual heat are two basic goals. This paper reports the formation of periodic subwavelength ripples on a silicon surface induced by a single shaped 800 nm femtosecond laser pulse. Using periodic π -phase step modulation, a Gaussian pulse is shaped into a pulse train with varying temporal intervals in the range of 0.1–7.2 ps. The single shaped pulse is applied to a silicon surface to produce periodic subwavelength ripples. The results show that when the interval between two subpulses is greater than 0.9 ps, periodic ripples can be observed at the center of the ablation crater. Increasing the subpulse interval can effectively reinforce the formation of periodic ripples. The two-temperature model and Drude model (TTM–Drude model) are applied to study the evolution of the electron density, electron temperature, and lattice temperature after irradiation by a single shaped pulse. The results show that the temporally shaped femtosecond laser pulse can enhance the excitation of surface plasmon polaritons and the periodic energy deposition while reducing residual thermal effects on the silicon surface, eventually resulting in periodic ripples at the center of the ablation area.